Peran Alternatif Penyelesaian Sengketa dalam Melindungi Merek di Platform E-Commerce Indonesia - Tutuarima, Gabriella P.M; Tuasikal, Hadi (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2025)
The rapid proliferation of e-commerce in Indonesia has precipitated a substantial increase in trademark infringement disputes, thereby accentuating the inherent limitations of conventional litigation, which is characterized by its protracted duration, prohibitive costs, and formalistic procedures. The aim of the research is to the pivotal role of Alternative Dispute Resolution (ADR) in safeguarding trademarks within the Indonesian e-commerce domain, meticulously addressing current implementation challenges and proposing comprehensive optimization strategies. Employing a normative legal research methodology encompassing statutory, conceptual, and case approaches, this research undertakes an in-depth analysis of Law No. 30 of 1999 concerning Arbitration and ADR, as well as Law No. 20 of 2016 concerning Trademarks and Geographical Indications. The findings indicate that the practical implementation of ADR in e-commerce trademark disputes remains suboptimal. Primary impediments include a low level of legal awareness among brand owners, particularly Micro, Small, and Medium Enterprises (MSMEs), a constrained understanding of ADR procedures, and a conspicuous deficiency in integrated Online Dispute Resolution (ODR) infrastructure on local e-commerce platforms. To bolster ADR's effectiveness, this research advocates for the reinforcement of regulations that are more responsive to the evolving e-commerce landscape, an enhancement of legal literacy among business actors through targeted socialization and training initiatives, the robust development of ODR infrastructure directly linked to official ADR institutions, the fostering of synergistic collaboration among government bodies, ADR institutions, and e-commerce platform providers, and a concerted effort to fortify public trust in ADR outcomes. Ultimately, the optimization of ADR is anticipated to accelerate the efficient and effective resolution of trademark disputes, ensure legal certainty, and cultivate a modern legal culture within Indonesia's burgeoning digital trade ecosystem, thereby comprehensively protecting the rights of brand owners and fostering equitable digital commerce. [Perkembangan pesat e-commerce di Indonesia telah mengakibatkan peningkatan signifikan dalam sengketa pelanggaran merek, menyoroti keterbatasan litigasi konvensional yang memakan waktu, biaya tinggi, dan bersifat formalistik. Tujuan penelitian adalah untuk mengkaji peran penting Alternatif Penyelesaian Sengketa (ADR) dalam perlindungan merek di ranah e-commerce Indonesia, membahas tantangan implementasi saat ini dan mengusulkan strategi optimalisasi. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan kasus, penelitian ini menganalisis Undang-Undang Nomor 30 Tahun 1999 tentang Arbitrase dan ADR, serta Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis. Adapun hasil pelaksanaan ADR dalam praktik sengketa merek e-commerce masih belum optimal. Tantangan utama meliputi rendahnya kesadaran hukum pemilik merek, terutama UMKM, keterbatasan pemahaman terhadap prosedur ADR, dan kurangnya infrastruktur Online Dispute Resolution (ODR) yang terintegrasi di platform e-commerce lokal. Untuk meningkatkan efektivitas ADR, penelitian ini merekomendasikan penguatan regulasi yang lebih responsif terhadap e-commerce, peningkatan literasi hukum bagi pelaku usaha melalui sosialisasi dan pelatihan, pengembangan infrastruktur ODR yang kuat dan terhubung langsung dengan lembaga ADR resmi, mendorong kolaborasi antara pemerintah, lembaga ADR, dan platform e-commerce, serta memperkuat kepercayaan publik terhadap hasil ADR. Optimalisasi ADR diharapkan mampu mempercepat penyelesaian sengketa merek secara efisien dan efektif, memberikan kepastian hukum, serta mendorong budaya hukum modern dalam ekosistem perdagangan digital Indonesia, pada akhirnya melindungi hak pemilik merek dan mempromosikan perdagangan digital yang adil.]